Using AHP-Entropy Method to Evaluate the Effect of Specific Surface Area of Manganese Slag on Concrete Properties : A Case Study on Sustainable Cementitious Materials - Feng, Li; Chee Khoon, Ng; Qiujin, Zhao (Seventh Sense Research Group, 2025)
This investigation examines the viability of employing Manganese Slag (MnS), an industrial by-product, as a sustainable Supplementary Cementitious Material (SCM) in concrete. MnS with four distinct Specific Surface Area (SSA) values (60, 120, 235, and 400 m²/kg) is assessed for its effects on workability, mechanical characteristics, and durability. Concrete specimens were fabricated by substituting different proportions of cement (by mass) with MnS, and their performance was evaluated through slump tests, compressive and flexural strength measurements, freeze-thaw resistance, sulfate attack, and chloride ion penetration analyses. The findings suggest that heightened SSA generally improves fluidity, strength, and durability, with better overall performance observed at 235-400 m²/kg SSA and 5-15% substitution. To find the optimal mixture design, the Analytic Hierarchy Process (AHP) and entropy methodology were utilized, and it was concluded that the most balanced overall performance of concrete was obtained at 235 m²/kg SSA and 10% substitution. This research establishes that MnS when appropriately processed and incorporated, can improve concrete properties while promoting sustainable industrial waste management. These outcomes advance the development of environmentally conscious construction materials and optimize SCM applications in cementitious systems.